Wild Mares : My Lesbian Back-to-the-Land Life - Hunter, Dianna, 1949- (Book collections on Project MUSE., 2018)
"Dianna Hunter was a softball-loving, working-class tomboy in North Dakota, surviving the threat of the Cuban Missile Crisis and Mutually Assured Destruction in the shadow of a strategic air command base. Communists and antiwar hippies were the enemy, but lesbians were a threat, too: they were unhealthy, criminal, and downright insane. It took Dianna a while to figure out that she was one, a little longer to discover how she fit in with her new communities in the city and the countryside. This is her story--a frank account by turns comic and painful of a well-behaved Midwestern girl finding her way through polite denial and repression and running head-on into the eye-opening events of the 1960s and '70s before landing on a dairy farm. A bumpy route takes Dianna to the Twin Cities, then to rural Minnesota and Wisconsin as--by way of the antiwar movement, women's liberation, and a dose of lesbian feminism--she and her friends try to establish a rural utopia free of sexual oppression, violence, materialism, environmental degradation--and men. They dream big, love as they see fit, and make do until they don't. Dianna buys a dairy farm and, with it, a new set of problems thanks to the Reagan-era farm crisis. A firsthand account of the lesbian feminist movement at its inception, Wild Mares is a deeply personal, wryly wise, and always engaging view of identity politics lived and learned in real life and, literally, on the ground, flourishing in the fertile soil of a struggling dairy farm in the American heartland."--Publisher description.